2015
DOI: 10.1186/s13104-015-1717-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological pattern of brain arteriovenous malformations (BAVMs) in a Tertiary Care Hospital in Bangladesh

Abstract: BackgroundWe have conducted this study to examine the clinical and morphological pattern of brain arteriovenous malformations (BAVMs) along with their treatment and short term outcome in a tertiary care hospital in Bangladesh. This retrospective chart review was carried out from the records of neuro-endovascular division at Department of Neurology, Dhaka Medical College Hospital (DMCH) from January 2010 to June 2013. A total 60 patients were evaluated. All the necessary information regarding the demographic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This is younger than the mean age of 37 years reported in a study conducted by Englot et al involving 440 patients with supratentorial AVM, and 30.3 years reported in another study conducted by Chowdhury et al involving 60 patients with brain AVMs. 21 , 22 The percentage of females (56.5%) reported to have residual AVM was almost similar to that of males (43.5%), which is consistent with data from the study conducted by Englot et al (48.6% were females and 51.4% were males). 21 …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is younger than the mean age of 37 years reported in a study conducted by Englot et al involving 440 patients with supratentorial AVM, and 30.3 years reported in another study conducted by Chowdhury et al involving 60 patients with brain AVMs. 21 , 22 The percentage of females (56.5%) reported to have residual AVM was almost similar to that of males (43.5%), which is consistent with data from the study conducted by Englot et al (48.6% were females and 51.4% were males). 21 …”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with other data showing that AVM is slightly more frequently found on the left when compared to the right cerebrum and more likely to be located supratentorially than infratentorially. 21 , 22 Supratentorially, our study found that the frontal lobe was the most common site for residual AVM (40.9% of supratentorial sites), followed by the temporal (18.2%), parietal (18.2%) and lastly occipital (13.6%) lobe. This is consistent with data showing the rate of AVM being highest in the frontal lobe (39.3%) followed by the temporal (27.4%), parietal (20.2%) and lastly occipital (13.1%) lobe.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations